Ghana, Savelugu-Nanton Household Survey Dataset, 2004 - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
In 2000, UNICEF–Ghana and IFPRI agreed upon a program of action research to evaluate the scope for food-based strategies to reduce micronutrient undernutrition in Ghana. The food-based strategies were planned as one component of UNICEF’s broader Integrated Community Based Development (ICBD) program. Although UNICEF had been operating its ICBD program in other districts, the food-based micronutrient strategies were first introduced as part of the ICBD program in Savelugu/Nanton District. The 2004 Savelugu/Nanton Household Survey was collected by the International Food Policy Research Institute (IFPRI) in collaboration with the Food and Nutrition Security Unit (FNSU) at the University for Development Studies (UDS), which is based in Tamale, northern Ghana. It is a cross-sectional survey that, when paired with the baseline survey conducted in 2001, formed the basis for an IFPRI-led impact evaluation of interventions sponsored by the United Nations Children’s Fund (UNICEF) to increase the micronutrient content of young children’s diets. The 2001 baseline household and community survey is also available from IFPRI at http://www.ifpri.org/data/Ghana02.asp.